Analisis Daya Saing Sektor Pariwisata dalam Meningkatkan Kunjungan Wisatawan di provinsi Lampung - Riskiya Dina Paramita; Indah Purwoningsih; Siti Musaroh Maydiana Alpa; Indah Septia Lestari; Berchah Pitoewas; Abdul Halim (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Lampung Province, especially Bandar Lampung City, is essentially trying to increase competitiveness through the tourism sector. Government policies in Bandar Lampung City have a strategic role in developing service quality and destination readiness as well as striving for an advanced and competitive tourism sector in increasing tourist visits to Lampung Province. This study aims to analyze the competitiveness of the tourism sector to increase tourist visits to tourist destinations in Lampung Province through exploring the role of tour guide training, developing CHSE (clean, healthy, safety, and environment) standard home stays, and utilizing digital technology in promoting destinations in Lampung. This research was conducted through in-depth interviews with the parties involved and using a descriptive qualitative approach as well as observation. Through in-depth interviews and the results of observations that have been carried out, it has been proven that building or striving for the competitiveness of the tourism sector to increase tourist visits in Lampung Province can strengthen the capability of providing quality services to tourists, having a level of tourist trust in visiting tourist destinations and digital-based promotions through social media which are essentially very significant in expanding the reach and awareness of destinations.  All of these strategies contribute to improving Lampung’s image as a competitive destination.